Adolescent and young adult acute lymphoblastic leukemia. Final results of the phase II pediatric‐like GIMEMA LAL‐1308 trial. Issue 3 (29th December 2020) - Testi, Anna Maria; Canichella, Martina; Vitale, Antonella; Piciocchi, Alfonso; Guarini, Anna; Starza, Irene Della; Cavalli, Marzia; De Propris, Maria Stefania; Messina, Monica; Elia, Loredana; Moleti, Maria Luisa; Martino, Bruno; et al.
Abstract: Adolescents and young adults (AYA) with acute lymphoblastic leukemia (ALL) represent a unique patient population with specific characteristics and needs. Growing evidences suggest that pediatric‐inspired approaches improve the outcome in AYA. These results prompted the design of a pediatric AIEOP‐BFM ALL 2000‐based regimen ‐ the GIMEMA LAL‐1308 protocol ‐ for newly diagnosed AYA (range 18‐35 years) with Philadelphia negative (Ph‐) ALL. The protocol included minimal residual disease (MRD) analysis at two different time‐points (TP), that is, at the end of induction IA and consolidation IB, and a modulation in post‐consolidation intensity according to MRD. Seventy‐six patients were eligible between September 2010 and October 2014. The regimen was well tolerated, with 2.7% induction deaths and no deaths in the post‐consolidation phase. The complete response (CR) rate was 92%; the 48‐month overall survival (OS) and disease‐free survival (DFS) were 60.3% and 60.4%. Both OS and DFS were significantly better in T‐ALL than B‐ALL. A molecular MRD <10 −3 at TP1 was associated with a significantly better OS and DFS (77% vs 39% and 71.9% vs 34.4%, respectively);similar results were documented at TP2 (OS and DFS 74.5% vs 30.6% and 71.5% vs 25.7%, respectively). The LAL‐1308 results were compared to those from similar historic AYA populations undergoing the two previous GIMEMA LAL‐2000 and LAL‐0904 protocols. Both OS and DFS improved significantly compared to the two previous protocols. These results indicate that this pediatric‐inspired and MRD‐oriented protocol is feasible and effective for Ph‐ AYA ALL patients, and underline the prognostic value of MRD determinations at specific TPs.